Relationship Marketing as a Driver of Competitive Advantage in Service Industries - Salamatun Asakdiyah (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
Relationship marketing is increasingly important in the context of intensifying competition in service industries that are becoming more commoditized, where price-based differentiation and operational efficiency are easy to imitate and quickly lose their distinctiveness. This article aims to examine relationship marketing as a driver of competitive advantage by positioning it as a strategic capability that builds relational assets. The study adopts a qualitative, theory-based narrative review approach focused on cross-theory conceptual synthesis and interpretive analysis. The review identifies a consistent mechanism: relationship marketing practices—through meaningful communication, service consistency, service recovery, ethically grounded personalization, and facilitation of customer participation—develop trust, commitment, and customer engagement that accumulate into relationship quality. Stronger relationship quality then enhances loyalty, increases retention, creates switching costs (especially relational costs), and expands relational capital in the form of customer knowledge, reputation, referral networks, and learning loops that support service innovation. The main contribution of this article is a theoretical synthesis that integrates the Resource-Based View, Social Exchange Theory, and Service-Dominant Logic into a conceptual RM–competitive advantage model that is path dependent and difficult to imitate. Theoretically, the model clarifies the causal–conceptual pathway through which service advantage is formed, while managerially it emphasizes orchestrating service culture and relational capabilities, including the responsible use of technology.